KONFLIK ILLEGAL FISHING DI WILAYAH PERBATASAN INDONESIA-AUSTRALIA - Akhmad Solihin (Bogor Agricultural University, 2010)
The habits of Indonesian fisher who ride into the territory of the Australian fisheries often causing fluctuative relations between two countries, because repressive action of the Australian Government's apparatus. Therefore, the purpose of this study are: to assess the economic interest of fisher when get into the fishery regions of Australia, to analyze the offense of illegal fishing, and to get the eradication strategies of illegal fishing in two countries agreement areas. This study is a descriptive analysis, using a normative juridical approach which is equipped with comparative approaches. Based on the analysis yielded that 1) sea cucumbers and sharks are the main target of Indonesian fisher, wherein the value of profits from sea cucumbers of AU 14,000-AU 30,000, 2) illegal fishing violation occurred, i.e.; breach of the agreement not only operating areas, the utilization of fishery resources, environmental pollution, but also agents of illegal immigrants, 3) eradication of illegal fishing through the establishment of a legal approach by arbitration forming, and economic approach with alternative livelihoods development.